Performa Performa Usaha Ternak Sapi Potong di Distrik Masni Kabupaten Manokwari: Business Performance of Beef Cattle in Masni District Manokwari Regency - Barakhiel W. Apasedanya; Muhammad Jen Wajo; Irba U. Warsono (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2023)
Abstract  This study aims to determine the business performance of beef cattle farmers in terms of livestock production and productivity and the income of farmers from beef cattle business. The research was conducted descriptively with survey techniques through interviews and field observations. Primary data was taken by conducting interviews with farmers or those who run beef cattle business, extension workers, and stakeholders in the field of animal husbandry. The observed variables included maintenance, housing, feeding, reproductive system and BCS as well as cattle farming business analysis. The data obtained were analyzed descriptively to determine the important values (means, maximum value, minimum value and standard deviation) and presented in tabular form. The t-test was carried out to determine conclusively the existence of the change phenomenon at the beginning of raising and now (late). The results of the study show that the performance of beef cattle business in Masni District has enormous potential as indicated by an efficient livestock production system, a high reproduction system and a profitable livestock business analysis value. The results of the t test show that there is a significant increase for the population and also the price with a B/C Ratio value was 1.9. Keywords: Business analysis; Cattle; Livestock production; Reproductive efficiency   Abstrak  Penelitian bertujuan mengetahui performa usaha peternak sapi potong dari segi produksi dan hasil pendapatan peternak dari usaha sapi potong. Penelitian dilakukan secara deskriptif dengan teknik survei melalui wawancara dan observasi lapangan. Data primer diambil dengan melakukan wawancara terhadap peternak atau yang menjalankan usaha ternak sapi potong, penyuluh, dan stake holder dibidang peternakan. Varibabel yang diamati meliputi pemeliharaan, perkandangan, pemberian pakan, sitem reproduksi, BCS (Body Condition Score) serta analisis usaha peternakan sapi. Data yang diperoleh dianalisis secara deskriptif untuk mengetahui nilai-nilai penting (means, nilai maksimum, nilai minimum dan standar deviasi) serta disajikan dalam bentuk tabel. Uji t dilakuan untuk mengetahui secara meyakinkan keberadaan fenomena perubahan saat awal beternak dan saat ini (akhir). Hasil penelitian menunjukkan bahwa performa usaha ternak sapi potong di Distrik Masni Kab. Manokwari memiliki potensi yang sangat besar. Hal ini ditunjukkan oleh sistem produksi ternak yang efisien, indeks reproduksi yang tinggi dan nilai analisa usaha ternak yang menguntungkan. Hasil Uji t menunjukkan bahwa ada peningkatan yang signifikan untuk populasi dan harga dengan nilai B/C Ratio adalah 1.9. Kata kunci: Analisa usaha; BCS; Efisiensi reproduksi; Performa usaha; Produksi ternak